HELICOBACTER PYLORI AND CARDIOVASCULAR DISEASE: THE ROAD TO THE HEART IS THROUGH THE STOMACH? - A. K. Martusevich; Zh. G. Simonova; E. I. Tarlovskaya (Российский кардиологический журнал, 2012)
The paper analyses the Russian and international evidence on the potential role of Helicobacter pylori infection in the development and progression of cardiovascular disease. The authors discuss the existing statistical evidence of this association, its pathogenetic mechanisms, and the effectiveness of preventive eradication treatment. Based on the literature data and the original research findings, the authors propose a new complex concept of the pathogenesis of Helicobacter pyloriassociated cardiovascular disease.